Alternative dispute resolution and freedom of information cases in the Council for Transparency - Rojas Corral, Hugo (Derecho Público Iberoamericano, 2016)
This paper describes the improvements in the management of freedom of information cases applied by the Council for Transparency (CPLT) in Chile. In the first part is presented the origin and the objectives of the alternative dispute resolution mechanisms applied by the CPLT, and the results achieved in the 2010 pilot plan. In the second part the current situation is critically evaluated, identifying difficulties, opportunities, and recent proposals. The respective working processes in the Legal Department of the CPLT are also described. From a methodological point of view, firsthand data have been collected and interviews have been conducted in the CPLT. This experience can be useful for other countries when resolving freedom of information cases, and also to promote alternative dispute resolution mechanisms in case management systems in the public sector.